VP189 Hemolysis Induced By Modern Infusion Pumps During Blood Transfusion. (12th January 2018) - Boileau, Jean-Christian; Lafrenière, Renée; Thibault, Louis; Carrier, Nathalie; De Grandmont, Marie-Joëlle; Beauregard, Patrice; Poder, Thomas
Abstract : INTRODUCTION: Following a first field evaluation conducted in 2013, we found that hemolysis can be induced by infusion pumps during blood transfusion. Actually, limited data is available on the risk of hemolysis associated with the most used infusion pumps in Quebec hospitals: InfusomatSpace (peristaltic), Plum A+TM (piston) and ColleagueCXE (shuttle). METHODS: Staff from the blood bank and the Health Technology Assessment (HTA) unit in our hospital collaborated in 2016 to assess the hemolysis and potassium level (that is, a blood test sensitive to hemolysis) induced by the use of the three infusion pumps mentioned above. Measurements were taken for each pump at five flow rates, from 30 to 450 ml/hour, and were compared with measurements taken before using the pumps. Tests were conducted with 135 red blood cell (RBC) units. RBC units were aged from 10 to 28 days. RESULTS: The shuttle- and piston-type pumps resulted in low hemolysis levels. The peristaltic-type pump produced significantly more hemolysis. However, the absolute value of hemolysis remained within the range recommended by the regulatory agencies in North America and Europe. Potassium levels did not increase with the use of the pumps. CONCLUSIONS: The collaboration between the blood bank and the HTA unit led to the conclusion that modern infusion pumps widely used in Quebec hospitals produce non-threatening levels of hemolysis during blood transfusion. This finding is important to ensure safe practices.